Fluid intelligence, trait emotional intelligence and academic performance in children with different intellectual levels. (2nd January 2021) - Li, Danfeng; Shi, Jiannong
ABSTRACT: This study examined the effects of fluid intelligence and trait emotional intelligence (trait EI) on academic performance in primary school-aged intellectually gifted and average children (8–11 years of age). One hundred and four average children and eighty gifted children were administered a Raven's Standard Progressive Matrices and a Trait Emotional Intelligence Questionnaire-Child Form. The results demonstrated that intellectually gifted children showed better academic performance than did average children in math, Chinese and English. Fluid intelligence and trait EI played different roles in predicting gifted and average children's academic performance, particularly in math and Chinese. Specifically, gifted children's academic performance was associated only with fluid intelligence, whereas average children's academic performance was related to both fluid intelligence and trait EI; trait EI had an incremental validity after controlling for fluid intelligence in predicting the average children's academic performance. The present study enhances our understanding of how cognitive and emotional abilities interact in intellectually gifted and average children's academic performance.